Coleta de recursos glucídios por vespas sociais: mecanismos que regem seu padrão de atividade diário - Sá, Cassia Alves de (2013)
The daily activity pattern of social wasps can be influenced by different mechanisms such as environmental restrictions or interspecific interactions. However, the importance of interspecific interactions on the determination of the daily activity patterns may decrease on habitats with high environmental complexity. In this sense, we evaluated two hypotheses in order to understand what factors affect the daily activity patterns of social wasps: 1) The abundance overlap of different species during the day is lower when environmental complexity is greater, and 2) Thermal restrictions may constrain wasp activity. We counted the abundance of several wasp species foraging throughout the day on extrafloral nectaries in two plantations of caupi bean: on esurrounded by a pasture matrix (low structural complexity) and the other surrounded by fruit trees (high structural complexity). Afterwards, we evaluated the abundance overlap during the day, the abundance variations per hour and the preferential time of start and end of day activity. Temporal overlapping between species during the day was high for both plantations. The majority of species had a bimodal abundance pattern, with one abundance peak during the morning and the other during the afternoon. Species of major size started their activity during later hours, while species of minor size were active on every hour. These results indicate two scenarios: first, competition seems to below in these communities and second, temperature seems to be particularly restrictive for the activity of species of greater size.